(untitled) (Conversatoria Linguistica, 2019)
The article presents the results of the survey regarding teachers’ statements on pupils with learning difficulties and academically more able pupils. According to gathered materials most of teachers’ utterances were phrased with the impersonal form. The first person form was used very rarely. 5 out of 33 respondents (15%) used the first person form in their utterances more than once. Every respondent (100%) uttered multiple expressions of judgmental and interpretational nature despite being asked for observations. In nearly half of the cases (48%) no expressions describing teachers’ personal feelings were used.